The Testing Effect and Far Transfer: The Role of Exposure to Key Information - van Eersel, Gerdien G.; Verkoeijen, Peter P. J. L.; Povilenaite, Migle; Rikers, Remy (Frontiers in Psychology, 2016)
Butler (2010: Experiment 3) showed that retrieval practice enhanced transfer to a new knowledge domain compared to rereading. The first experiment of the present study was a direct replication of Butler’s third experiment. Participants studied text passages and then either reread them three times or went through three cycles of cued recall questions (i.e., retrieval practice) with feedback. As in Butler’s experiment (2010), an advantage of retrieval practice on the final far transfer test emerged after one week. Additionally, we observed an advantage of retrieval practice on the final test administered after five minutes. However, these advantages might have been due to participants in the retrieval practice condition receiving focused exposure to the key information (i.e., the feedback) that was needed to answer the final test questions. We therefore conducted a second experiment in which we included the retrieval practice condition and the reread condition from our first experiment, as well as a new reread-plus-statements condition. In the reread-plus-statements condition, participants received focused exposure to the key information after they had reread a text. As in Experiment 1, we found a large effect on far transfer when retrieval practice was compared to rereading. However, this effect was substantially reduced when retrieval practice was compared to the reread-plus-statements condition. Taken together, the results of the present experiments demonstrate that Butler’s (2010) testing effect in far transfer is robust. Moreover, focused exposure to key information appears to be a significant factor in this far transfer testing effect.